Exploring the effect of skim milk on the membrane stability of frozen–thawed Inner Mongolia cashmere goat sperm based on proteomics - Xue, Shan-hui; Xu, Bing-bing; Li, Wen-ze; Zhang, Jia-xin; Su, Rui (Frontiers in Cell and Developmental Biology, 2026)
IntroductionThe cryopreservation of semen from the Inner Mongolia cashmere goat, a valuable dual-purpose breed in China, results in a sharp decline in sperm motility, hindering genetic improvement and germplasm propagation. This study aimed to investigate the protective effects and underlying mechanisms of skim milk as a supplement in a cryopreservation extender.MethodsSkim milk was added stepwise (2%–3.6%) to an egg yolk–soy lecithin basal extender, with 2.8% identified as the optimal concentration. Tandem mass tag (TMT) quantitative proteomics, coupled with parallel reaction monitoring (PRM) validation, was employed to analyze the proteomic profiles of post-thaw sperm and elucidate homeostatic mechanisms related to sperm membrane stability.ResultsThe addition of 2.8% skim milk significantly increased post-thaw sperm motility to 68.23%, reduced ultrastructural abnormalities, elevated acrosomal integrity by 18.7%, and decreased lipid peroxidation by 29% (P < 0.05). Proteomic analysis identified 32 differentially expressed proteins. Gene Ontology (GO) enrichment revealed significant involvement in processes related to purine ribonucleoside triphosphate metabolism and transmembrane transporter activity. KEGG pathway analysis indicated predominant enrichment in energy metabolism and signal transduction pathways. PRM validation confirmed that proteins NDUFA8, PGAM2, ACTL7A, PRXL2B, ATP6V0C, and LELP1 exhibited expression patterns consistent with the proteomic data, serving as core biomarkers for skim milk-mediated membrane stabilization.DiscussionThis study provides the first proteomic-level evidence that skim milk enhances the cryotolerance of Inner Mongolia cashmere goat spermatozoa. The mechanism involves the modulation of an energy–membrane protein network, which stabilizes sperm membranes during cryopreservation. The identified proteins establish molecular biomarkers for optimizing semen cryopreservation protocols in this breed.